Juvenile paget's disease in an Iranian kindred with vitamin D deficiency and novel homozygous TNFRSF11B mutation. (21st May 2013) - Saki, Forough; Karamizadeh, Zohreh; Nasirabadi, Shiva; Mumm, Steven; McAlister, William H; Whyte, Michael P
ABSTRACT Juvenile Paget's disease (JPD) is a rare heritable osteopathy characterized biochemically by markedly increased serum alkaline phosphatase (ALP) activity emanating from generalized acceleration of skeletal turnover. Affected infants and children typically suffer bone pain and fractures and deformities, become deaf, and have macrocranium. Some who survive to young adult life develop blindness from retinopathy engendered by vascular microcalcification. Most cases of JPD are caused by osteoprotegerin (OPG) deficiency due to homozygous loss‐of‐function mutations within the TNFRSF11B gene that encodes OPG. We report a 3‐year‐old Iranian girl with JPD and craniosynostosis who had vitamin D deficiency in infancy. She presented with fractures during the first year‐of‐life followed by bone deformities, delayed development, failure‐to‐thrive, and pneumonias. At 1 year‐of‐age, biochemical studies of serum revealed marked hyperphosphatasemia together with low‐normal calcium and low inorganic phosphate and 25‐hydroxyvitamin D levels. Several family members in previous generations of this consanguineous kindred may also have had JPD and vitamin D deficiency. Mutation analysis showed homozygosity for a unique missense change (c.130T>C, p.Cys44Arg) in TNFRSF11B that would compromise the cysteine‐rich domain of OPG that binds receptor activator of NF‐κB ligand (RANKL). Both parents were heterozygous for this mutation. The patient's serum OPG level was extremely low and RANKL level markedly elevated. She responded well to rapid oral vitamin D repletion followed by pamidronate treatment given intravenously. Our patient is the first Iranian reported with JPD. Her novel mutation in TNFRSF11B plus vitamin D deficiency in infancy was associated with severe JPD uniquely complicated by craniosynostosis. Pamidronate treatment with vitamin D sufficiency can be effective therapy for the skeletal disease caused by the OPG deficiency form of JPD.